Microbiological control of cellular products: the relevance of the cellular matrix, incubation temperature, and atmosphere for the detection performance of automated culture systems - Günther, Susanne-Katharina; Mutters, Nico T.; Günther, Frank (Transfusion medicine and hemotherapy, 2020)
Background: The microbiological control of cellular products sometimes causes significant procedural issues for quality control laboratories. According to the European Pharmacopoeia (EP), the microbiological control of cellular products requires a 7- to 14-day incubation period at two different incubation temperatures using aerobic and anaerobic growth media. However, the suitability of these test conditions for efficient quality control can be influenced by many conditions, such as the expected microbial spectrum of contamination or the texture and composition of the cellular product. Because of interference, direct inoculation and membrane filtration as reference methods of pharmacopoeia are largely unsuitable for the microbiological control of cellular products; therefore, alternative and, above all, automated methods are the focus of interest. Objective: The aim of our study was to evaluate the method suitability and possible effects of cell matrix, incubation temperature, and oxygen pressure on the detection performance of automated culture systems.Methods: The BacT/ALERT® 3D TM Dual T system (bioMérieux, Nürtingen, Germany) was used to evaluate the factors influencing automated microbiological control of cellular products. The tests were performed using microbial strains recommended by the EP for microbiological method suitability testing and additional relevant possible contaminants of human-derived stem-cell products under varying culture and cell matrix conditions. Results: All contaminants were detected by the system in the required period of 2-5 days. Low incubation temperatures (22°C) had overall negative effects on the detection kinetics of each type of microbial contamination. The adverse effects of the accompanying cell matrix on the detection properties of the system could be compensated in our study by incubation at 32°C in both the aerobic and the anaerobic culture conditions. Conclusion: Automated culture techniques represent a sufficient approach for the microbiological control of cellular products. The negative effects of the cell matrix and microbial contamination on the detection performance can be compensated by the application of variable culture conditions in the automated culture system.